Strategies of persuasion in Herodotus' Histories and Genesis-Kings: evoking reality in ancient narratives of a past - Tyrell, Eva (Journal for the study of Judaism, 2020)
Intro -- Contents -- Acknowledgements -- Part 1 Premises and Concepts -- Chapter 1 Persuasion and Comparison -- 1 A Comparative Approach -- 2 The Writers' Awareness for Their Craft -- 3 Characteristics of the Sources -- 3.1 Tradition Literature versus Known Author -- 3.2 Points of Similarity in the Selected Sources -- Chapter 2 Method, Objectives, Theory -- 1 Do Historical Narratives Employ Specific Narrative Strategies? -- 2 Comparing Texts while Granting Them Different Criteria of Validity and Plausibility -- 2.1 Rüsen's Theory: Universal Areas of Plausibility in Historical Thought -- 2.2 My Approach -- 3 Strategies of Persuasion as Accessibility Relations -- 4 Excursus: Ancient Greek Philosophy and Rhetorical Theory -- 5 Limitation to Narratorial Discourse -- 6 Additional Premises -- 7 The Constitutive Role of the Recipient -- 8 Usefulness of the Distinction between Narrator and Author -- Part 2 Fundamentals of Narrative Structurein Herodotus' Histories and Genesis-Kings -- Chapter 3 Highly Different Modes of Narration and Mediacy -- 1 Introduction -- 2 Mediacy in Gen-Kings and Herodotus -- 2.1 The Narrator Speaking in the First Person -- 2.2 A Term Designating the Work -- 2.3 Narratorial References to 'Himself' as the Narrator -- 2.4 Insights into the Narrator's Thought Processes and Method -- 3 Two Contrasting Modes of Mediation -- Chapter 4 Connecting and Disconnecting Story-World and Discourse-World -- 1 Indication of Temporal Distance between the Discourse-Now and the Past -- 2 The Proportion of Discursive Parts -- 2.1 Objects as Connectors of Story-World and Discourse-World -- 3 The Use of Direct and Indirect Speech -- 4 Characters Indirectly Addressing the Extradiegetic Audience -- 5 Narrative Mode and Source Criticism -- Part 3 Varied Functions of Objects as Means of Persuasion -- Introduction.